Digital Marketing untuk Meningkatkan Efisiensi Usaha Batu Bata di Kabupaten Banyuasin - Handayani, Febria Sri; Hadiwijaya, Hendra; Putri, Meidyan Permata; Andita, Mirza Putri (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2025)
The intense competition in the era of globalization has increased pressure on SMEs to undergo digital transformation. Lan Brick Craftsmen in Banyuasin Regency is one of the SME that is striving to implement digitalization in their business to increase the sales. This activity aims to transfer knowledge, provide Website as a Digital Marketing tool, and providing training and mentoring to ensure the effective adoption of digital processes, particularly Digital Marketing. This training program covers basic digital literacy, e-commerce, and Digital Marketing. Based on feedback from Lan Brick Craftsmen, the training and mentoring implemented in this program has greatly helped them understand and implement Digital Marketing in the business, which they previously had little understanding of. As a result of implementing Digital Marketing, Lan Brick's product sales increased by 25%.